2012
DOI: 10.1055/s-0032-1315812
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results in Scalp Tissue Expansion in Children

Abstract: Tissue expansion remains a good technique to repair large lesions of the scalp in children. The deformation of the skull spontaneously resolves and does not have any consequence on brain growth. The widening of the scar is a common problem in children but can be reduced by suture in two layers associated with local reconstruction. Moreover, young children do not keep any unpleasant memory of this period and are not susceptible to social pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Reported by two studies of tissue expansion in children. 47,54 Impact of surgery on QoL of patients during the week after the intervention Not at all: 0.0%, A little: 70.4%, A lot: 25.9%, Very much: 3.7%. Reported by Ceballos-Rodríguez ( n = 136) in a study of tissue expansion, serial excision, and skin grafting.…”
Section: Suicide Attemptmentioning
confidence: 99%
See 2 more Smart Citations
“…Reported by two studies of tissue expansion in children. 47,54 Impact of surgery on QoL of patients during the week after the intervention Not at all: 0.0%, A little: 70.4%, A lot: 25.9%, Very much: 3.7%. Reported by Ceballos-Rodríguez ( n = 136) in a study of tissue expansion, serial excision, and skin grafting.…”
Section: Suicide Attemptmentioning
confidence: 99%
“…Patient age, CMN location, and extent of excision NR. 38,47,49,54 Hyperpigmentation 12.9% (21/163) 35,40,55 One study reported only unspecified results Warner ( n = 40) 'nine patients required additional surgical procedures due to growth-induced scar contractures, hypertrophy, hirsutism, and pigment changes'. 53 Three studies reported narrative results concerning color of the surgical site 1) Ma ( n = 11) 'a close match in terms of tissue colour'.…”
Section: Melanoma Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…Tissue expansion has been described extensively as a useful technique for covering large scalp defects [ 1 2 3 4 ] [ Figure 1 ]. Tissue expansion is ideal for scalp defects because the skull acts as a rigid base for the expander and the overlying scalp is thick; this helps reduce the risk of thinning and extrusion of the implant.…”
Section: Introductionmentioning
confidence: 99%